(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
This comprehensive article provides an in-depth analysis of the governmental structure of the United States of America, focusing on the three key branches: Legislative, Executive, and Judicial. It delves into the distinct roles and functions of each branch, emphasizing the critical role of the US Congress within the Legislative Branch. The article offers a clear breakdown of the Senate and the House of Representatives, detailing their responsibilities and powers